NEW SPECIES OF PARINARI Aublet (Rosaceae-Chrysobalanoideae) - A. J. G. H. KOSTERMANS (Reinwardtia, 1965)
The following is an account and description of new species of Asiatic and one Fijian species of Parinari Aublet, originally intended to be included into a forthcoming monographic treatment of the Asiatic Parinari species Dr.Yan Prance (New York Botanical Garden) has informed me, that his revision and new classification of genera of the Chrysobalanoideae will be published soon and consequently I have deferred the publication of my monograph to a later date.The species here are treated in a conservative way and described as belonging to the genus Parinari sensu lato; between brackets I have added the section to which the species belongs.